Youth’s Trust in Online News Media About The Corona Virus Issues - Andini Nur Bahri (Jurnal Komunika Islamika : Jurnal Ilmu Komunikasi dan Kajian Islam, 2020)
News and information about the corona virus has become the topic most often consumed by the public lately despite the declining public trust in the media both traditional media and online media. It also affects the younger generation in consuming media and trusting the credibility of a media. This study aims to determine the trust of students who have studied science related to the media, namely students of Islamic communication and broadcasting UINSU on online news websites about the corona virus and how is the relationship between the selection of online news website with trust in media. This study uses descriptive correlational methods with as many respondents 228 people. This research found that most of the students chose national online news websites in getting news about corona and there was no significant relationship between online news site selection and students' belief that the online news websites  published accurate facts about corona virus.